Mathematical word problem solving abilities of hearing-impaired students. Issue 1 (February 2021) - Suarsana, I M; Sudatha, I G W; Mahayukti, G A; Apsari, R A
Abstract: One of the useful methods to facilitate the students in understanding the benefits and real application of mathematics in real life is by formulating the problem in words. Unfortunately, the previous studies found that students with hearing difficulties usually have limited vocabularies and it becomes a barrier to them in understanding the given context in word problems. Therefore, this study aims at describing the ability of students with hearing-impaired problem in solving mathematical word problems by examining the mathematical skills performed. Since the purpose is to describe a phenomenon, qualitative approach with case study design was deliberately chosen as the method of the study. The subject of the research was eight seventh grade students of School for the Hearing-Impaired in Singaraja, Bali-Indonesia. The data were collected through written test and interview. Afterwards, the data were analysed qualitatively using descriptive method. The results show that the students with hearing-impaired problem were struggling in solving mathematical word problems due to the lack of understanding of the problem and mathematical concepts. Furthermore, there is no tendency for the students with lower level of hearing difficulties to perform better in solving word problems.